Citizenship Education Model For The Establishment Of Legal Awareness To Implement The Social Functions Of Land Rights - Rejekiningsih, Triana (Sebelas Maret University, 2016)
This study aims to explore: (1) The importance of citizenship education to shape of legal awareness of citizensâ; (2) the essence of the implementation of the principle of the social function of land rights; and (3) Competence citizensâ awareness applying the principle of the social function of land rights. This study used a qualitative approach, the method of socio legal research, by looking at the effectiveness of the law in society. Data analysis techniques in this study conducted with interactive analysis of data items, namely the data collection, data reduction, the data presentation and conclusion. Conclusions The results were obtained: (1) Civics is very important to establish the legal awareness of citizensâ, who can participate and be responsible for applying the law, to achieve the greatest prosperity of the people; (2) The essence of the application of the principle of the social function of land rights be realized through the use of land that does not harm the public interest, land tenure the which does not exceed the maximum limit of land ownership, working on their own land with the characteristics of the soil, preventing the ways extortion and maintain the land, including adding and prevent damage fertility; and (3) Competence citizensâ awareness applying the principle of the social function of land rights consist of legal knowledge of citizensâ against the principal of social function of land rights, the attitude of citizens to comply with the rights and obligations of land, and establish skills of citizens in harnessing and using the land, as living resources together to achieve the greatest prosperity of the people